Research Trends in Philosophy of Science in Education: A Bibliometric Study of the Recent Period - Witzir Sumadisastro; Babang Robandi; Diki Fahrizal; Nor Shahila Mansor (Yayasan Keluarga Guru Mandiri, 2025)
This study examines research trends in the philosophy of science within the educational context, focusing on its ontological, epistemological, and axiological dimensions. Using a bibliometric approach, 868 academic publications from 2010 to 2024 were analyzed, sourced from Scopus and Google Scholar with keywords such as “Philosophy of Science in Education” and “Educational Philosophy and Knowledge. Data were processed and visualized using VOSviewer to identify patterns, themes, and collaboration networks. The findings revealed six key clusters: philosophical foundations in educational practices, ontological and epistemological dimensions in educational research, historical and scientific perspectives, problem-solving approaches, axiological dimensions, and Islamic perspectives in educational philosophy. These results highlight the growing integration of interdisciplinary perspectives, critical thinking, and value-based education to address global challenges such as technological advancements and cultural shifts. This study contributes to the literature by offering insights into the evolving role of philosophy in education, emphasizing the importance of ethical leadership, cultural inclusivity, and sustainable educational practices. The findings provide actionable guidance for policymakers, educators, and researchers in designing curricula and pedagogical strategies that align with 21st-century educational needs while fostering moral and social responsibility.